Cellulose nanofibers (CNF) as reinforcement for cementitious matrices: a systematic literature review - Aquino Rocha, Joaquin Humberto; Farias, Lidianne do Nascimento; Siqueira Thaís Pinto Lobo (Revista ALCONPAT, 2022)
The aim of this study is to conduct a systematic literature review of the last five years on the use of cellulose nanofibers (CNF) in cementitious composites. The main production and dispersion methods are presented with emphasis on their effect on the behavior of cement-based materials. The study considered the influence of CNF on the fresh and hardened state properties: rheology, hydration, compressive strength, flexural strength, fracture energy, among others. CNF show positive effects on mechanical properties. However, further research is still necessary to optimize the production and pretreatment processes of CNF, establishing relationships regarding the durability of composites with CNF, and identifying possible environmental impacts of their use.